2020
DOI: 10.2169/internalmedicine.4178-19
|View full text |Cite
|
Sign up to set email alerts
|

Deferasirox Might Be Effective for Microcytic Anemia and Neurological Symptoms Associated with Aceruloplasminemia: A Case Report and Review of the Literature

Abstract: The patient was a 64-year-old man presented with difficulty in walking, articulation, and swallowing, as well as cognitive impairment. He had refractory microcytic anemia and diabetes mellitus. His serum levels of iron, copper, and ceruloplasmin were low. Magnetic resonance imaging suggested iron deposition in the basal ganglia, thalami, cerebellar dentate nuclei, and cerebral and cerebellar cortices. He was diagnosed with aceruloplasminemia after a ceruloplasmin gene analysis. Iron chelation therapy with defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Based on a literature review, it was suggested that chelation treatment in neurologically symptomatic patients rarely leads to improvement while a long-term treatment in neurologically asymptomatic patients may prevent the occurrence of neuropsychiatric symptoms [151]. Others have documented improvement of neurological symptoms in 50% of patients with neurological symptoms [152]. An aggregated case study analyzed chelation treatment outcomes in 24 symptomatic and 24 asymptomatic patients and concluded that clinical improvement was described in almost half of the symptomatic patients while chelation postponed symptom onset by approximately 10 years in asymptomatic patients [153].…”
Section: Neurodegenerations With Brain Iron Accumulation (Nbia) Groupmentioning
confidence: 99%
“…Based on a literature review, it was suggested that chelation treatment in neurologically symptomatic patients rarely leads to improvement while a long-term treatment in neurologically asymptomatic patients may prevent the occurrence of neuropsychiatric symptoms [151]. Others have documented improvement of neurological symptoms in 50% of patients with neurological symptoms [152]. An aggregated case study analyzed chelation treatment outcomes in 24 symptomatic and 24 asymptomatic patients and concluded that clinical improvement was described in almost half of the symptomatic patients while chelation postponed symptom onset by approximately 10 years in asymptomatic patients [153].…”
Section: Neurodegenerations With Brain Iron Accumulation (Nbia) Groupmentioning
confidence: 99%
“…The iron chelator deferasirox (DFX) can improve anemia, as observed in patients with transfusional iron overload, such as patients with myelodysplastic syndrome (MDS), 1-4 myeloproliferative neoplasms, 5 aplastic anemia, 2,6 pure red cell aplasia, 7 and the iron metabolism disorder aceruloplasminemia. 8 How DFX improves anemia is unclear. It may increase erythropoietin production, improve iron availability for hematopoietic tissue, 9 and modify the bone marrow (BM) microenvironment by reducing oxidative stress 10,11 and inflammation.…”
mentioning
confidence: 99%